Gonadotropin-Dependent Precocious Puberty: Neoplastic Causes and Endocrine Considerations. (27th January 2011) - Stephen Stephen, Matthew D. Matthew D.; Zage Zage, Peter E. Peter E.; Waguespack Waguespack, Steven G. Steven G.
Abstract : Premature activation of the hypothalamic-pituitary-gonadal (HPG) axis manifests as gonadotropin-dependent precocious puberty. The mechanisms behind HPG activation are complex and a clear etiology for early activation is often not elucidated. Though collectively uncommon, the neoplastic and developmental causes of gonadotropin-dependent precocious puberty are very important to consider, as a delay in diagnosis may lead to adverse patient outcomes. The intent of the current paper is to review the neoplastic and developmental causes of gonadotropin-dependent precocious puberty. We discuss the common CNS lesions and human chorionic gonadotropin-secreting tumors that cause sexual precocity, review the relationship between therapeutic radiation and gonadotropin-dependent precocious puberty, and finally, provide an overview of the therapies available for height preservation in this unique patient population.